2000
DOI: 10.1074/jbc.275.33.25231
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II Is Required for Mitoxantrone to Signal Nuclear Factor κB Activation in HL60 Cells

Abstract: Topoisomerase II is a target for a number of chemotherapeutic agents used in the treatment of cancer. Its essential physiological role in modifying the topology of DNA involves the generation of transient double-strand breaks. Anti-cancer drugs, such as mitoxantrone, that target this enzyme interrupt its catalytic cycle and give rise to persistent double strand breaks, which may be lethal to a cell. We investigated the role of such lesions in signaling the activation of the transcription factor nuclear factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
49
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 54 publications
1
49
0
1
Order By: Relevance
“…These agents can exert their cytotoxic mode of action by inducing DNA damage irrespective of the cell cycle phase. Mitoxantrone and doxorubicin have been described to intercalate with DNA at high concentrations, but also to inhibit Topoisomerase II, thereby leading to persistant double-strand breaks of DNA (Bodley et al, 1989;Boland et al, 2000). Cisplatin has been shown to alkylate DNA and to lead to the activation of caspase 8 with subsequent initiation of a caspase cascade (Ferreira et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…These agents can exert their cytotoxic mode of action by inducing DNA damage irrespective of the cell cycle phase. Mitoxantrone and doxorubicin have been described to intercalate with DNA at high concentrations, but also to inhibit Topoisomerase II, thereby leading to persistant double-strand breaks of DNA (Bodley et al, 1989;Boland et al, 2000). Cisplatin has been shown to alkylate DNA and to lead to the activation of caspase 8 with subsequent initiation of a caspase cascade (Ferreira et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, the activation of NF-kB is strictly dependent on the presence of an intact nucleus and a drug-sensitive version of topoisomerase I or II enzyme, showing the intimate link between the formation of double-strand breaks (DSBs) and NF-kB activation. [25][26][27] Topoisomerases are enzymes that control the degree of DNA supercoiling. Type I topoisomerases (targeted by CPT) create transient single-strand breaks in DNA, necessary for the induction of transcription, while topoisomerase II enzymes (inhibited by etoposide-like and doxorubicin-like drugs) are more involved in DNA replication and cell division and therefore create transient DSBs.…”
mentioning
confidence: 99%
“…31,34 Recent evidence demonstrates that ATM is also required for the activation of NF-kB in response to various genotoxic stress insults, expanding the known ATM-dependent network. 27,[37][38][39] Although the NF-kB response to IR is still controversialmany authors utilize IR doses that are high above clinically relevant doses (r2 Gy) 40 and clear differences in sensitivity to IR are observed between primary and transformed cell types 41 -different groups independently demonstrated that the NF-kB response to IR in ATM-deficient cells is abrogated, both in transformed cell types 37,38 as well as in primary mouse tissues. 38 Furthermore, also CPT and doxorubicin appear to induce NF-kB activation via an ATM-dependent pathway.…”
mentioning
confidence: 99%
See 2 more Smart Citations